2017
DOI: 10.1007/978-94-024-1079-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by Taurine on HBCD-Induced Apoptosis in PC12 Cells

Abstract: Hexabromocyclododecane (HBCD) is a widely used brominated flame retardant (BFR). Because of their presence in human issues, including brain tissue, concern has been raised on their possible neurotoxicity. Presently, we explored the neuroprotection of taurine against HBCD-induced apoptotic damages in PC12 cells. Cells were pre-treated with taurine before HBCD exposure and the viability was assayed via the methyl-thiazolyl-tetrazolium (MTT) method. Apoptotic features were observed with Hoechst 33342 staining. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Bax, cleaved Caspase-3, and cleaved PARP are pro-apoptotic proteins, while Bcl-2 is an anti-apoptotic protein. 29,30 Results showed that hypoxia increased expression of Bax, cleaved Caspase-3, and cleaved PARP and decreased expression of Bcl-2. Differently, TPP administration reversed the expression trend, which could explain the finding in apoptosis.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Bax, cleaved Caspase-3, and cleaved PARP are pro-apoptotic proteins, while Bcl-2 is an anti-apoptotic protein. 29,30 Results showed that hypoxia increased expression of Bax, cleaved Caspase-3, and cleaved PARP and decreased expression of Bcl-2. Differently, TPP administration reversed the expression trend, which could explain the finding in apoptosis.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Induced growth of BG‐1 ovarian cancer cells by 17beta‐estradiol or various endocrine disrupting chemicals was reversed by resveratrol via downregulation of cell cycle progression.Treatment of BG‐1 cells with HBCDDs resulted in an increase of cell growth.Li et al. (2017c). Neuroprotection by Taurine on HBCD‐Induced Apoptosis in PC12.Exposure of PC12 cells to 10 μM HBCDDs reduced protein expression of Bcl‐2, increased expression in Bax protein and activity of caspase‐3.…”
Section: Appendix D – Mode Of Action Studiesmentioning
confidence: 99%
“…Treatment of BG-1 cells with HBCDDs resulted in an increase of cell growth. Li et al (2017c). Neuroprotection by Taurine on HBCD-Induced Apoptosis in PC12.…”
Section: Referencementioning
confidence: 99%